2013
DOI: 10.1093/neuonc/not138
|View full text |Cite
|
Sign up to set email alerts
|

Physical functioning in pediatric survivors of childhood posterior fossa brain tumors

Abstract: Pediatric survivors of PFBTs demonstrated decreased physical functioning, most notably in Balance. These data underscore the need for further research and implementation of physical activity programs aimed specifically at approaches to minimize physical limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 51 publications
4
76
1
4
Order By: Relevance
“…All but one of the studies demonstrated high retention rates (82%), acceptability (expressed as enjoyment and/or satisfaction with the intervention), and feasibility (as evidenced by moderate to high adherence and retention rates). One of these PA studies, which enrolled 13 Swedish cancer survivors, ages 7–17 years who were treated for brain tumors, investigated the effect of active video gaming on PA, a reduction in which is a common late effect in patients with brain tumors . Participants were randomized to active video gaming on a Nintendo Wii (30 min/day, 5 days/week for 10 weeks) with coaching via video conferencing, or to a wait‐listed control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All but one of the studies demonstrated high retention rates (82%), acceptability (expressed as enjoyment and/or satisfaction with the intervention), and feasibility (as evidenced by moderate to high adherence and retention rates). One of these PA studies, which enrolled 13 Swedish cancer survivors, ages 7–17 years who were treated for brain tumors, investigated the effect of active video gaming on PA, a reduction in which is a common late effect in patients with brain tumors . Participants were randomized to active video gaming on a Nintendo Wii (30 min/day, 5 days/week for 10 weeks) with coaching via video conferencing, or to a wait‐listed control group.…”
Section: Resultsmentioning
confidence: 99%
“…One of these PA studies, which enrolled 13 Swedish cancer survivors, ages 7-17 years who were treated for brain tumors, investigated the effect of active video gaming on PA, a reduction in which is a common late effect in patients with brain tumors. 24,25 Participants were randomized to active video gaming on a Nintendo Wii (30 min/day, 5 days/week for F I G U R E 1 Flowchart illustrating the process of literature search and extraction of studies meeting the inclusion criteria 10 weeks) with coaching via video conferencing, or to a wait-listed control group. Although mean daily time spent in moderate-to-vigorous PA did not change, the study was deemed acceptable by participants and resulted in a significant increase in participants' body coordination over the 12-week time period.…”
Section: Study Outcomesmentioning
confidence: 99%
“…Wolfe et al reported lower‐than‐expected peak oxygen uptake during exercise (31.8 [SD, 7.2] mL/kg/minute vs 49.3 [SD, 7.9] mL/kg/minute) among 12 adolescent survivors of posterior fossa tumors (mean age, 14.41 years [SD, 1.86 years]). Piscione et al documented strength deficits among 30% of another group of adolescent survivors of posterior fossa tumors (30 individuals; mean age, 11.4 years [SD, 4.1 years]).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the diverse nature of tools used across studies to measure HRQOL, we were unable to quantitatively differentiate between particular facets of this construct. However, previous research has shown that pediatric CNS tumor survivors may be especially at risk for both physical and social limitations 3,79. Thus, interventions on these domains may indeed positively impact overall HRQOL.…”
mentioning
confidence: 99%